Effects of exercise‐induced beta‐hydroxybutyrate on muscle function and cognitive function. Issue 3 (6th February 2021) - Kwak, Seong Eun; Bae, Jun Hyun; Lee, Ji Heun; Shin, Hyung Eun; Zhang, DiDi; Cho, Sung Chun; Song, Wook
Abstract: Recent studies have shown that exercise improves skeletal muscle and cognitive function by stimulating the secretion of numerous molecules. In particular, previous studies have suggested that exercise‐induced beta‐hydroxybutyrate (BHB) release might improve skeletal muscle and cognitive function, but to date these studies have been limited to cell and animal models. Therefore, we aimed to determine how an exercise‐induced increase in BHB affects skeletal muscle and cognitive function at a cellular level, in an animal model, and in humans. The effects of BHB on skeletal muscle and cognitive function were determined by treating C2C12 and C6 cell lines with BHB, and by measuring the skeletal muscle and serum BHB concentrations in aged mice after endurance or resistance exercise. In addition, serum BHB concentration was measured before and after high‐speed band exercise in elderly people, and its relationships with muscle and cognitive function were analyzed. We found that BHB increased cell viability and brain‐derived neurotrophic factor expression level in C6 cells, and endurance exercise, but not resistance exercise, increased the muscle BHB concentration in aged mice. Furthermore, the BHB concentration was positively related to skeletal muscle and cognitive function. Exercise did not increase the serum BHB concentration in the elderly people and BHB did not correlate with cognitive function, but after excluding the five people with the highest preexisting serum concentrations of BHB, the BHB concentrations of the remaining participants were increased by exercise, and the concentration showed a tendency toward a positive correlation with cognitive function. Thus, the BHB released by skeletal muscle following endurance exercise may improve muscle and cognitive function in animals and humans. Abstract : Exercise upregulated DBHB level in skeletal muscle in mice and skeletal muscle cell. Also, DBHB effected to cognitive function as well.